Current knowledge, status, and future for plant and fungal diversity in Great Britain and the UK Overseas Territories. Issue 5 (29th September 2020) - Clubbe, Colin; Ainsworth, A. Martyn; Bárrios, Sara; Bensusan, Keith; Brodie, Juliet; Cannon, Paul; Chapman, Ted; Copeland, Alison I.; Corcoran, Marcella; Dani Sanchez, Michele; David, John C.; Dines, Trevor; et al.
Societal Impact Statement: We rely on plants and fungi for most aspects of our lives. Yet plants and fungi are under threat, and we risk losing species before we know their identity, roles, and potential uses. Knowing names, distributions, and threats are first steps toward effective conservation action. Accessible products like field guides and online resources engage society, harnessing collective support for conservation. Here, we review current knowledge of the plants and fungi of the UK and UK Overseas Territories, highlighting gaps to help direct future research efforts toward conserving these vital elements of biodiversity. Summary: This review summarizes current knowledge of the status and threats to the plants and fungi of Great Britain and the UK Overseas Territories (UKOTs). Although the body of knowledge is considerable, the distribution of information varies substantially, and we highlight knowledge gaps. The UK vascular flora is the most well studied and we have a relatively clear picture of its 9, 001 native and alien taxa. We have seedbanked 72% of the native and archaeophyte angiosperm taxa and 78% of threatened taxa. Knowledge of the UKOTs flora varies across territories and we report a UKOTs flora comprising 4, 093 native and alien taxa. We have conserved 27% of the native flora and 51% of the threatened vascular plants in Kew's Millennium Seed Bank, UK. We need a better understanding of the conservation status of plants in the wild, and progress toward completion or updating national red lists varies. Site‐based protection of key plant assemblages is outlined, and progress in identifying Important Plant Areas analyzed. Knowledge of the non‐vascular flora, especially seaweeds remains patchy, particularly in many UKOTs. The biggest gaps overall are in fungi, particularly non‐lichenized fungi. Considerable investment is needed to fill these knowledge gaps and instigate effective conservation strategies. Abstract : We rely on plants and fungi for most aspects of our lives. Yet plants and fungi are under threat, and we risk losing species before we know their identity, roles, and potential uses. Knowing names, distributions and threats are first steps towards effective conservation action. Accessible products like field guides and online resources engage society, harnessing collective support for conservation. Here we review current knowledge of the plants and fungi of the UK and UK Overseas Territories, highlighting gaps to help direct future research efforts towards conserving these vital elements of biodiversity.